Relationship Between Functional Activity And Nutritional Status, Manual Ability And Intelligence In Children With Cerebral Palsy - Rosdiana, Ika; Daniswari, Verina Gian; Sura, Getri; Ariestiani, - (International Journal of Human and Health Sciences (IJHHS), 2022)
a